DIGITAL GOVERNANCE: AN ALLY TO THE PRINCIPLE OF ADMINISTRATIVE MORALITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The use of new technologies has enabled major transformations in society, whether in customs, labor and socio-political relations. Within the scope of the relationship between the citizen and the Public Administration, information technology is capable of enabling a more agile management, with greater transparency and democracy, all with the purpose of meeting the administrative principles imposed by the constitution, among them, the principle of morality administrative. Thus, through a bibliographic review, we seek to deepen the advantages of using technologies by Public Administration, with the aim of enhancing the principle of administrative morality.